Perubahan Bunyi Bahasa Proto Austronesia Ke Bahasa Minangkabau - Mukramah, Mukramah (Educompassion: Jurnal Integrasi Pendidikan Islam dan Global, 2025)
This study aims to find out what sound changes occur from the Proto Austronesian language to the Minangkabau language. This study uses a qualitative approach from data taken from 300 basic understandings. The methods and techniques used in data collection are cakap, which is an interview or direct observation in the field. After that, note-taking and recording techniques were also carried out. This study was conducted in Medan which is located in Kampung Padang. The results of the study indicate that the sound changes from the Proto Austronesian language to the Minangkabau language include changes in the sounds of Metathesis, Apheresis, Syncope, Apocope, Prothesis, Epenthesis, Paragog.